2006
DOI: 10.1111/j.1365-2133.1975.tb06735.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of water content of stratum corneum

Abstract: SUMMARY The water content of human stratum corneum has been measured gravimetrically in vitro in relation to relative humidity (RH) and temperature. Water content increased with increasing RH. Stratum corneum water content increased 50% when the temperature was raised from 20 to 35°C at RH below 60%. Temperature dependence decreased with increasing RH until there was essentially no temperature dependence at 90% RH. The conclusion is that temperature changes could significantly affect water content in vivo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 4 publications
1
16
0
3
Order By: Relevance
“…A study on human skin showed that the SC water content decreased together with temperature, and that the relationship was stronger with low RH (<60%) (Table ) .…”
Section: Low Temperature Negatively Affects Skin Barrier Functionmentioning
confidence: 99%
“…A study on human skin showed that the SC water content decreased together with temperature, and that the relationship was stronger with low RH (<60%) (Table ) .…”
Section: Low Temperature Negatively Affects Skin Barrier Functionmentioning
confidence: 99%
“…Therefore, conclusions based on these results may not reflect the actual energetics of sorption of water in SC. Spencer et al27 performed a similar set of studies with the opposite result, that is, ΔH iso was found to be positive (endothermic reaction) although the magnitude still decreased with increasing water content. The limitations of these results draw our attention to calorimetry, which can produce direct information about the heat of sorption.…”
Section: Introductionmentioning
confidence: 96%
“…This gradual water flux is dependent, to a slight extent, upon the thickness of the stratum corneum (being smaller for thicker tissue layers within each region [35,36]), the size of the intervening corneocytes (inverse relationship [29]), local tissue temperature (greater when warmed [37-39]), the boundary-layer water vapour pressure (greater at lower vapour pressures [13,39,40]) and even posture (greater when upright [33]). However, it is not influenced by changes in cutaneous blood flow, unless there is a corresponding elevation in local tissue temperature [13].…”
Section: Introductionmentioning
confidence: 99%